Method for observing internal defect of steel material

Ultrasonic fatigue testing and fracture surface analysis allow for the simultaneous observation and evaluation of inclusions and gaps in steel, addressing the underestimation of their harmful effects.

JP2025001624APending Publication Date: 2025-01-08SANYO SPECIAL STEEL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2024005499
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-06-20
Filing Date
2024-01-17
Publication Date
2025-01-08

AI Technical Summary

Technical Problem

Existing methods fail to simultaneously observe and evaluate the properties of inclusions and gaps within steel materials, leading to underestimation of their harmful effects on the lifespan of steel components.

Method used

A method involving ultrasonic fatigue testing to break a steel specimen, observe the properties of inclusions and gaps on the fracture surface, using ultrasonic flaw detection to identify defect locations, and analyzing the fracture surface with scanning electron microscopy.

Benefits of technology

Enables simultaneous observation of inclusion properties and gap states, allowing for more effective methods to mitigate their harmful effects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025001624000001_ABST
    Figure 2025001624000001_ABST
Patent Text Reader

Abstract

To simultaneously grasp the property of an inclusion and the state of a gap in the boundary between an inclusion and a mother material in a steel material.SOLUTION: The method for observing an internal defect of a steel material includes the steps of: collecting a main test piece (2) from a steel material (1); breaking the main test piece (2) by an ultrasound fatigue test and obtaining a fracture surface; and observing the state of an inclusion in a starting point on the fracture surface and the state of a gas in the boundary between the inclusion and the mother material.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for simultaneously observing nonmetallic inclusions present inside a steel material and gaps present at the boundaries between the nonmetallic inclusions and the base material. [Background technology]

[0002] Steel parts such as bearings may break earlier than expected (hereinafter also referred to as "short-life spalling") even when used under proper lubrication conditions. Short-life spalling is caused by nonmetallic inclusions (hereinafter also referred to as "inclusions") contained in steel. Inclusions are inevitably generated in the refining, casting, and solidification processes of steel manufacturing. In the rolling and forging processes downstream of these processes, the shape and dispersion state of the inclusions and the state of the boundary between the inclusions and the base material, that is, the gaps (hereinafter also referred to as "gaps") generated at the boundary, may change, which may change the harmfulness to the life of the steel part (hereinafter also referred to as inclusion harmfulness).

[0003] It is important to understand the properties of inclusions in order to reduce the number of inclusions in steel, and it is necessary to understand the state of gaps in order to reduce the harmfulness caused by inclusions. The properties of inclusions include various properties that affect the harmfulness of inclusions, such as the composition, shape, size, and frequency of presence of inclusions. The state of gaps includes the shape and size of the gaps. Short-life spalling originating from inclusions usually occurs from a position slightly inside the surface of the steel part. For example, if the steel part is a bearing, high shear stress occurs slightly inside the raceway that is in rolling contact with the rolling body (balls, rollers, etc.), and fatigue (rolling fatigue) progresses due to the repeated action of this stress. If harmful inclusions or gaps are included in the area of ​​action of the high shear stress described above, cracks generated from them will trigger short-life spalling.

[0004] Therefore, it is particularly important to grasp the state of inclusions and gaps immediately below the rolling contact between bearing parts made of steel. Non-Patent Document 1 discloses a method for predicting the maximum diameter of inclusions in a reference volume by microscopy and extreme value statistics. Patent Document 1 discloses a method for predicting the maximum diameter of inclusions in steel. In this method, the diameter of inclusions present on the fracture surface in an ultrasonic fatigue test is actually measured. Based on this diameter value, the maximum diameter is calculated by extreme value statistics. Patent Document 2 also discloses a method for predicting the maximum diameter of inclusions by ultrasonic fatigue testing and extreme value statistics. In this method, a test piece charged with hydrogen is subjected to ultrasonic fatigue testing. Hydrogen charging is performed for the purpose of promoting fracture of the test piece by utilizing hydrogen embrittlement.

[0005] None of the above-mentioned methods simultaneously observes and comprehensively evaluates inclusions and internal defects, i.e., gaps, and therefore tend to underestimate the harmful effects that affect the lifespan. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2009-281738 A [Patent Document 2] JP 2020-34292 A [Non-patent literature]

[0007] [Non-Patent Document 1] "Metal Fatigue: Effects of Micro Defects and Inclusions" by Takayoshi Murakami, published by Yokendo in 1993 Summary of the Invention [Problem to be solved by the invention]

[0008] The object of the present invention is to provide a method for observing internal defects that can grasp the properties of inclusions and the state of gaps present in steel (for example, the properties of inclusions and the state of gaps present directly below the rolling contact area between steel parts). [Means for solving the problem]

[0009] In order to solve the above problems, the method for observing internal defects in steel material according to the present invention includes the steps of: (A) taking a main test piece from the steel material; (B) fracturing the main test piece by ultrasonic fatigue testing to obtain a fracture surface; and (C) observing the properties of an inclusion present at the origin on the fracture surface and the state of a gap present at the boundary between the inclusion and the base material.

[0010] In step (A), a steel bar can be used as the steel material. Here, the main test piece can be taken so that the longitudinal direction of the steel bar and the longitudinal direction of the main test piece are perpendicular to each other.

[0011] In the step (B), a load having a stress of 550 MPa or more may be applied to the main test piece by an ultrasonic fatigue test. Effect of the Invention

[0012] According to the observation method of the present invention, the properties of inclusions and the state of gaps can be observed simultaneously on the fracture surface of the main test piece, which makes it possible to devise and develop more effective methods for improving the harmfulness of inclusions and gaps. [Brief description of the drawings]

[0013] [Figure 1] 1 is a flowchart illustrating a method for observing inclusions and gaps according to an embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic diagram showing a steel bar on which markings are formed. [Diagram 3] FIG. 2 is a diagram for explaining the position where a main test piece was taken from a steel bar. [Figure 4] FIG. 2 is a perspective view of the main test piece. [Diagram 5] FIG. 2 is a cross-sectional view of the main test piece. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] The observation method of the present invention will be described in detail below with reference to the drawings. The flow chart in Fig. 1 shows the procedure for observing the properties of inclusions and the state of gaps contained in a steel material.

[0015] (STEP 1) First, a bar-shaped steel material (hereinafter also referred to as steel bar) 1 is prepared. This steel bar 1 can be manufactured by forging, rolling, etc., a steel ingot, followed by cutting. However, the shape of the steel material prepared in STEP 1 is not limited to a bar shape, and it may have a shape different from a bar shape. Steel material refers to a primary product manufactured at an ironworks or steelworks, or an Nth-order product (where N is an integer of 2 or more) processed from a primary product at an ironworks, steelworks, or other facility, and includes steel parts.

[0016] As described later, a main test piece 2 is taken from the steel bar 1, and the location from which it is taken can be determined arbitrarily. For example, as described later in STEP 2 and STEP 3, a defect location identified by ultrasonic testing can be set as the location from which the main test piece 2 is taken. Here, if the defect location is not identified, STEP 2 and STEP 3 described later can be omitted.

[0017] When STEP 2 and STEP 3 are performed, the steel bar 1 may be subjected to a heat treatment for facilitating processing and a heat treatment for suppressing attenuation of ultrasonic waves during ultrasonic testing. Examples of this heat treatment include normalizing, annealing, and spheroidizing annealing. When the steel bar 1 is subjected to hot plastic processing, the surface may be cut or heat treated after the plastic processing in order to suppress attenuation of ultrasonic waves during ultrasonic testing. The conditions of these heat treatments can be determined based on the chemical composition of the steel material to be subjected to ultrasonic testing. As a means for determining these conditions, calculation of an equilibrium phase diagram using thermodynamic calculation software or verification by preliminary experiments can be used. If these conditions are already known in literature or materials, this known information may be used.

[0018] (STEP 2) An ultrasonic flaw detection test is performed on the steel bar 1 prepared in STEP 1. The ultrasonic flaw detection test device is equipped with an ultrasonic probe, which emits ultrasonic waves. The ultrasonic waves emitted from the ultrasonic probe are incident on the steel bar 1. If the steel bar 1 contains internal defects such as non-metallic inclusions, the ultrasonic waves will be reflected by these internal defects. The reflected waves (echoes from the internal defects) generated by this reflection are detected by the ultrasonic probe, and the internal defects are detected.

[0019] By emitting ultrasonic waves while moving relative to the steel bar 1, it is possible to inspect internal defects over a wide range of the steel bar 1. For example, the ultrasonic probe can be moved along the longitudinal direction of the steel bar 1, or along the end face (a surface perpendicular to the longitudinal direction of the steel bar 1) of the steel bar 1. Here, in the steel bar 1, a single internal defect may be detected, or multiple internal defects may be detected.

[0020] For ultrasonic testing, a direct contact method or a water immersion method can be used. Considering that stable transmission and reception of ultrasonic waves is possible, it is preferable to use the water immersion method. The frequency of the ultrasonic waves emitted from the ultrasonic probe is preferably 10 MHz or more and 50 MHz or less, more preferably 15 MHz or more and 50 MHz or less, and even more preferably 20 MHz or more and 50 MHz or less. By increasing the frequency of the ultrasonic waves to 15 MHz or more, the detection accuracy of internal defects can be further improved.

[0021] (STEP 3) Based on the test results of the ultrasonic flaw detection test, the location of the internal defect is identified. In other words, the location where the presence of an inclusion is suspected (hereinafter also referred to as the "detection location") is identified. When the detection location is identified, a marking K is formed on the surface of the steel bar 1 at a position corresponding to the detection location. FIG. 2 shows a perspective view (one example) of a steel bar 1 on whose surface a marking K is formed. In FIG. 2, an ultrasonic probe is moved on the surface of the steel bar 1 in the vertical direction (longitudinal direction of the steel bar) of FIG. 2, and the marking K is formed at the movement position of the ultrasonic probe when an internal defect is detected. Note that, although FIG. 2 shows the location of the marking K as one location, when multiple detection locations are identified, the marking K is formed at the surface positions of the steel bar 1 corresponding to each of the detection locations.

[0022] However, instead of the marking K, the detection location may be identified by electronic information (i.e., position information) for identifying the position of the internal defect in the steel bar 1. The marking K and the above-mentioned position information are used as processing position information when processing the main test piece 2 from the steel bar 1 using a processing device, as described below.

[0023] (STEP 4) A sampling step is carried out to sample the main test piece 2 from the steel bar 1. The sampling step includes rough processing, quenching and tempering, and finish processing. In the rough processing, the steel bar is subjected to cutting and the like. The hardness of the main test piece 2 is adjusted by quenching and tempering. The hardness of the main test piece 2 is preferably 450 HV or more, and more preferably 500 HV or more. By adjusting the hardness of the main test piece 2 to 450 HV or more and by carrying out hydrogen charging, which will be described later, it becomes easier to fracture the main test piece 2 from the inclusion as a starting point during ultrasonic fatigue testing.

[0024] Fig. 3 is a diagram for explaining the extraction position of the main test piece 2 in the steel bar 1, and is a diagram showing the positional relationship (one example) between the steel bar 1 and the main test piece 2. As shown in Fig. 3, it is preferable to extract the main test piece 2 so that the longitudinal direction of the steel bar 1 (the left-right direction in Fig. 3) and the longitudinal direction of the main test piece 2 (the up-down direction in Fig. 3) are perpendicular to each other. Here, when the marking K is formed in STEP 3, the position corresponding to the marking K is set as the extraction position of the main test piece 2.

[0025] The steel bar 1, which is the base material of the main test piece 2, is processed (rolled) while being stretched in its longitudinal direction, and depending on the composition of the inclusions, the inclusions tend to stretch in the longitudinal direction of the steel bar 1 during rolling, and tend to spread and distribute in the longitudinal direction of the steel bar 1. Furthermore, gaps present at the interface between the inclusions and the base material also tend to expand in the longitudinal direction (rolling direction) in which the steel bar 1 is stretched. Therefore, by making the longitudinal direction of the steel bar 1 and the longitudinal direction of the main test piece 2 perpendicular to each other, it becomes easier to comprehensively evaluate the properties of the inclusions and the state of the gaps in an observation of the fracture surface, which will be described later.

[0026] FIG. 4 is a perspective view of the main test piece 2 after finishing, and FIG. 5 is a cross-sectional view taken along the line X-X in FIG. 4. The main test piece 2 is formed in a dumbbell shape, and has a central portion 3 extending in a predetermined direction, a pair of large diameter portions 4 formed at both ends of the central portion 3, and a male thread portion 4A protruding from an end face of one of the large diameter portions 4. The central portion 3 has a straight portion 6 having a constant diameter, and a pair of tapered portions 8 formed at both ends of the straight portion 6. The male thread portion 4A is fastened to an ultrasonic horn of an ultrasonic fatigue tester in an ultrasonic fatigue test described later. In addition, if a male thread is formed on the ultrasonic horn, it is not necessary to form the male thread portion 4A on the main test piece 2, and a female thread portion that fastens to the male thread of the ultrasonic horn can be formed on the end face of one of the large diameter portions 4 of the main test piece 2. In addition, the shape of the main test piece 2 is not limited to the dumbbell shape shown in FIG. 4, and may be another shape.

[0027] (STEP5) Measure the resonance frequency of the main test piece 2. By applying mechanical or electrical vibration to the main test piece 2, the resonance frequency of the main test piece 2 can be measured.

[0028] (STEP 6) After connecting the ultrasonic fatigue tester and the main test piece 2 by fastening the male thread portion 4A of the main test piece 2 to the ultrasonic horn of the ultrasonic fatigue tester, the resonant frequency of the main test piece 2 is compared with a reference frequency to determine pass / fail. The reference frequency is the frequency of ultrasonic vibration applied to the main test piece 2 in the ultrasonic fatigue test described below. The pass / fail determination is made based on the degree of deviation between the resonant frequency of the main test piece 2 and the reference frequency.

[0029] Specifically, if the resonant frequency of the main test piece 2 is included within the allowable frequency band based on the reference frequency, the main test piece 2 is judged to be "passed", and if the resonant frequency of the main test piece 2 is outside the allowable frequency band, the main test piece 2 is judged to be "failed". The upper limit of the allowable frequency band is a value obtained by adding a predetermined frequency to the reference frequency, and the lower limit of the allowable frequency band is a value obtained by subtracting a predetermined frequency from the reference frequency. Here, the value added to and the value subtracted from the reference frequency may be the same value or may be different values.

[0030] For example, if the reference frequency of the ultrasonic fatigue tester is 20,000 Hz and the resonant frequency of the main test piece 2 is between 19,800 Hz and 20,200 Hz (within the allowable frequency band), the main test piece 2 is judged to have "passed". On the other hand, if the resonant frequency of the main test piece 2 is less than 19,800 Hz or more than 20,200 Hz, the main test piece 2 is judged to have "failed". By adopting an even stricter standard, the allowable frequency band can be set to between 19,970 Hz and 20,030 Hz. In this case, when the resonant frequency of the main test piece 2 is between 19,970 Hz and 20,030 Hz, the main test piece 2 is judged to have "passed".

[0031] (STEP7) If the main test piece 2 is determined to be unsatisfactory in STEP 6, the main test piece 2 is processed again to adjust the resonance frequency of the main test piece 2. A typical processing here is to change the length of the main test piece 2. By changing the length of the main test piece 2, the resonance frequency of the main test piece 2 can be changed. After the main test piece 2 is processed in STEP 7, the resonance frequency of the main test piece 2 is measured again in STEP 5 described above, and in STEP 6 described above, it is determined whether the resonance frequency of the main test piece 2 is within the allowable frequency band, thereby determining whether the main test piece 2 passes or fails. Here, the processes in STEP 7, STEP 5, and STEP 6 are repeated until the resonance frequency of the main test piece 2 is within the allowable frequency band.

[0032] (STEP8) Hydrogen is charged to the main test specimen 2 that has been judged to pass in STEP 6. Hydrogen charging can cause hydrogen embrittlement in the main test specimen 2. The main test specimen 2 that has been subjected to hydrogen embrittlement can be fractured with a small stress and a small number of repeated cycles in the ultrasonic fatigue test described below. Hydrogen charging is performed for the purposes of facilitating and speeding up fracture in the ultrasonic fatigue test, and reducing the impact of fracture on the fracture surface.

[0033] As the hydrogen charging method, any known method can be appropriately adopted, and examples thereof include the following methods (1) to (3). (1) The main test piece 2 is immersed in the electrolyte. (2) The main test piece 2 is exposed to a high-pressure hydrogen gas atmosphere. (3) Electrolysis is performed in an electrolyte using the main test piece 2 as the cathode.

[0034] When performing the electrolysis in (3) above, for example, an electrolyte in which 3 wt% sodium chloride and 0.3 wt% ammonium thiocyanate are added to pure water can be used. Since the diffusion coefficient of hydrogen atoms in steel is temperature dependent, if an electrolyte with a temperature higher than room temperature is used, hydrogen can be charged with high efficiency, i.e., in a shorter time. If the main test piece 2 contains a sufficiently large internal defect, the main test piece 2 will easily break, and hydrogen charging (STEP 8) can be omitted.

[0035] (STEP 9) An ultrasonic fatigue test is performed on the main test specimen 2 that has been charged with hydrogen in STEP 8. The hydrogen introduced into the main test specimen 2 by hydrogen charging (STEP 8) is gradually released into the atmosphere, so the hydrogen contained in the main test specimen 2 gradually decreases. If the ultrasonic fatigue test is performed shortly after hydrogen charging (STEP 8), the main test specimen 2 containing sufficient hydrogen can be subjected to the ultrasonic fatigue test, and the ultrasonic fatigue test can be performed in a state where hydrogen embrittlement occurs.

[0036] In ultrasonic fatigue testing, tensile loads and compressive loads are alternately and repeatedly applied to the main test piece 2 connected to an ultrasonic horn by ultrasonic vibration. The direction of action of these loads is the axial direction (longitudinal direction) of the main test piece 2. As the load is applied, stress is generated in the main test piece 2, and it is preferable to apply a load to the main test piece 2 so that a stress of 550 MPa or more is generated in the main test piece 2. Note that the stress generated in the main test piece 2 may be adjusted to a higher stress to promote rapid fracture, on the premise that heat generation in the main test piece 2 during the ultrasonic fatigue testing as described below is suppressed.

[0037] During the ultrasonic fatigue test, the main test piece 2 generates heat and rises in temperature due to internal friction caused by repeated stress loading. This temperature rise promotes hydrogen release from the main test piece 2 and also inhibits brittle fracture of the main test piece 2, preventing the completion of the ultrasonic fatigue test. Therefore, it is preferable to suppress the temperature rise of the main test piece 2. Here, for example, the temperature rise of the main test piece 2 can be suppressed by blowing cooled air onto the main test piece 2. The temperature rise of the main test piece 2 can also be suppressed by intermittently inputting ultrasonic vibrations to the main test piece 2.

[0038] Since the degree of temperature rise due to internal friction depends on the hardness and alloy composition of the main test piece 2, it is possible to suppress the temperature rise of the main test piece 2 while suppressing heat generation due to internal friction by selecting an appropriate load based on the properties of the main test piece 2. Here, it is preferable to perform all of the above-mentioned air blowing, intermittent input of ultrasonic vibration, and appropriate selection of the test load.

[0039] In the main test specimen 2 to which the above-mentioned load is applied, stress concentration occurs in the inclusions and gaps. As the load is repeatedly applied, fatigue fracture occurs in the inclusions and gaps contained in the evaluation volume of the main test specimen 2 (corresponding to the volume of the straight portion 6 in the main test specimen 2 shown in Figure 4). This fatigue fracture causes the main test specimen 2 to break, resulting in a fracture surface. Usually, fracture of the main test specimen 2 occurs in a plane perpendicular to the direction in which the load is applied (the axial direction of the main test specimen 2).

[0040] (STEP10) The fracture surface of the main test piece 2 is observed to confirm the properties of the inclusions and the state of the gaps. By observing the starting point of the fracture, the properties of the inclusions and the state of the gaps can be confirmed at the same time. One method for confirming the fracture surface is observation with a scanning electron microscope (SEM), and based on the observation results, for example, the diameter (size) of the inclusions and the cross-sectional area of ​​the gaps can be calculated. Then, by image analysis of the observed image, the individual cross-sectional areas of the inclusions and the gaps and the total cross-sectional area can be determined.

[0041] The properties of the inclusions observed are not limited to their diameter (size). For example, the chemical composition of the inclusions may be analyzed using an energy dispersive X-ray analyzer or wavelength dispersive X-ray analyzer attached to a scanning electron microscope. This chemical composition can be used as data showing the characteristics of the inclusions contained in the steel material.

[0042] In addition, when checking the properties of the inclusions, it is possible to check not only the fracture surface (surface) of the main test piece 2 but also the inside of the main test piece 2 (i.e., the inside of the inclusions). For example, by exposing the inside of the inclusions using an ion milling method, the exposed surface can be observed.

[0043] Ion milling is a processing method in which an argon ion beam accelerated in a vacuum is irradiated onto the main test piece 2 (inclusion), thereby flicking off atoms and molecules in the irradiated area, thereby cutting the main test piece 2 (inclusion). Ion milling methods include planar milling and cross-sectional milling. Planar milling is a method in which an argon ion beam is irradiated obliquely onto the irradiated surface of the main test piece 2. Cross-sectional milling is a method in which a mask (shielding plate) is placed on the irradiated surface of the main test piece 2, and an argon ion beam is irradiated perpendicularly onto the irradiated surface.

[0044] On the other hand, when the main test piece 2 is taken so that the longitudinal direction of the steel bar 1 and the longitudinal direction of the main test piece 2 are perpendicular to each other as shown in FIG. 3, in the above-mentioned STEP 2, it is preferable to detect internal defects by moving the ultrasonic probe along the end face of the steel bar 1 (a surface perpendicular to the longitudinal direction of the steel bar 1).

[0045] Increasing the frequency of the ultrasonic waves emitted from the ultrasonic probe makes it easier to improve the detection accuracy of internal defects, but it also makes it easier to narrow the detectable area of ​​internal defects. Specifically, when the ultrasonic probe is moved along the longitudinal direction of the steel bar 1, the detection accuracy of internal defects can be ensured in the surface layer of the steel bar 1, but the detection accuracy of internal defects tends to decrease toward the center in the radial direction of the steel bar 1. If the position of the internal defect is identified in a state where the detection accuracy has decreased, the actual position of the internal defect will deviate from the straight portion 6 of the main test piece 2 (the portion where the above-mentioned fracture surface is obtained), making it difficult to generate a fracture surface in the straight portion 6.

[0046] By moving the ultrasonic probe along the end face of the steel bar 1, internal defects can be detected with the same detection accuracy in the entire radial area of ​​the steel bar 1. This makes it easier to detect internal defects while ensuring detection accuracy, and prevents the position of the internal defect from shifting from the straight portion 6 of the main test piece 2.

[0047] When the ultrasonic probe is moved along the end face of the steel bar 1, the accuracy of detecting internal defects tends to decrease the further away from the end face of the steel bar 1 in the longitudinal direction of the steel bar 1. However, if the position of the end face is adjusted by cutting the steel bar 1, etc., it becomes easier to detect internal defects. [Explanation of symbols]

[0048] 1 steel bar 2 Main test piece 3 Central part 4 Large diameter part 4A Male thread 6 Straight section 8 Tapered section

Claims

1. (A) taking a main test piece from a steel material; (B) fracturing the main test piece by ultrasonic fatigue testing to obtain a fracture surface; (C) observing the properties of the inclusions present at the origins on the fracture surfaces and the state of gaps present at the boundaries between the inclusions and the base material; A method for observing internal defects in a steel material, comprising:

2. 2. The method for observing internal defects in a steel material according to claim 1, wherein in the step (A), a steel bar is used as the steel material.

3. The method for observing internal defects in steel material according to claim 2, characterized in that in step (A), the main test piece is taken so that the longitudinal direction of the steel bar and the longitudinal direction of the main test piece are perpendicular to each other.

4. A method for observing internal defects in steel material as described in any one of claims 1 to 3, characterized in that in step (B), a load having a stress of 550 MPa or more is applied to the main test piece by ultrasonic fatigue testing.

Citation Information

Patent Citations

  • Prediction method of largest inclusion diameter in steel product, and estimation method of rolling fatigue life of steel product

    JP2009281738A

  • Method for predicting maximum inclusion diameter in steel product by ultrasonic fatigue test

    JP2020034292A